2018
DOI: 10.1038/s41467-018-06035-1
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature polarized spin-photon interface based on a semiconductor nanodisk-in-nanopillar structure driven by few defects

Abstract: Owing to their superior optical properties, semiconductor nanopillars/nanowires in one-dimensional (1D) geometry are building blocks for nano-photonics. They also hold potential for efficient polarized spin-light conversion in future spin nano-photonics. Unfortunately, spin generation in 1D systems so far remains inefficient at room temperature. Here we propose an approach that can significantly enhance the radiative efficiency of the electrons with the desired spin while suppressing that with the unwanted spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 59 publications
(46 reference statements)
0
19
0
1
Order By: Relevance
“…Недавно появилось сообщение об исследовании спинзависимой рекомбинации при комнатной температуре в периодической структуре, образованной нанодисками GaAsN, встроенными в одномерные наноколонны из GaAs [21]. Установлено, что в каждом диске располагается 2−3 дефекта, ответственных за рекомбинацию.…”
Section: заключениеunclassified
“…Недавно появилось сообщение об исследовании спинзависимой рекомбинации при комнатной температуре в периодической структуре, образованной нанодисками GaAsN, встроенными в одномерные наноколонны из GaAs [21]. Установлено, что в каждом диске располагается 2−3 дефекта, ответственных за рекомбинацию.…”
Section: заключениеunclassified
“…We have previously shown that the formation of selfassembled QDs is very efficient in novel GaNAs NWs, adding to numerous attractive properties of dilute nitride alloys [24][25][26][27][28]. The formation of these QDs is caused by clustering of N atoms, which leads to strong electron confinement facilitated by the giant bowing in the band-gap energy in dilute nitrides [22,29].…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional periodic nanostructures (nanogratings) are one of the most fundamental devices and have been widely applied in electronic, optical, magnetic, and biological applications 1117 . One notable application is the diffraction grating in spectrometer, where the grating period determines the angular dispersion and resolution of the system.…”
Section: Introductionmentioning
confidence: 99%